(untitled) (JURNAL IBU DAN ANAK, 2022)
Pain in the first stage of labor is a normal process felt by mothers in labor with different pain intensities in each individual. There are many methods to provide comfort for maternity mothers in managing the pain they feel, one of which is by giving birth ball and counterpressure exercises. The purpose of this study was to determine the effectiveness of the birth ball and counterpressure on the response to labor pain in the active phase of the 1st stage. The type of research used is Quasy Experiment with Two Group Pretest and Posttest design. The population in this study were all mothers giving birth at PMB Siti Julaeha Pekanbaru City from January to April 2022. The sample in this study was taken using the accidental-sampling method with a total of 10 women giving birth who were given a birth ball and 10 women who gave birth who were given counterpressure. The method of data collection is the observation method, to assess the response to labor pain intensity before and after the intervention. From the results of the Mann-Whitney U test, it showed that there was a significant difference between birth ball and counterpressure on labor pain (p = 0.001). Of the two techniques that are more effective in reducing labor pain is counterpressure with the results of the Mean Rank value of pain intensity which is 14.40. It is suggested to midwives to prioritize the counterpressure method in provding comfort to help manage the pain felt by mother in labor.